Situação nutricional de escolares de 7 a 10 anos de Santa Maria de Jetibá - Espírito Santo - Justo, Glaucia Figueiredo (2011)
The nutritional transition process by which Brazil crosses points to a trend of increasing overweight and obesity and reduction of underweight. The aim of this study was to estimate the prevalence of nutritional deficiencies in school children aged 7 to 10 years in Santa Maria de Jetibá, ES, Brazil, and investigate the sociodemographic and dietary habits related to them, the sample consisted of 901 schoolchildren 445 (49.4%) boys and 456 (50.6%) girls. We collected sociodemographic, anthropometric and nutrition in schools. Nutritional status was classified according to Body Mass Index (BMI) for age (WHO, 2007). The statistical analysis used the chi-square and logistic regression (significance of 0.05%). We studied 901 schoolchildren and found a prevalence of underweight 3.4%, 14.7% overweight and 4.6% for obesity. It was observed that the rural location (OR = 0.523, 95% CI 0.368 to 0.781) and the habit of having breakfast (OR 0.508, 95% CI 0.302 to 0.918) are protective factors against overweight in children. In a subsample of 487 students, who had the form completed by their parents, a study was conducted to identify factors associated with obesity. It was found that habit of having breakfast (OR = 0.12, 95% CI 0.03 to 0.44), responsible working in agriculture (OR = 0.125, 95%CI 0.30-0.314) and breastfeeding (OR = 0.018, CI95% 0.001-0.362) are protective factors for obesity. Nutrition education focuses on eating habits, the school environment, campaigns and specific policies for breastfeeding could help to prevent overweight and obesity. The changing context of the reduction of malnutrition may be a reflection of the universal access of the population to essential services such as education, health and sanitation.